Investigation of neurological manifestations in patients admitted with COVID-19 infection at Teresina Emergency Hospital (Research, Society and Development, 2022)
Objective: to analyze the frequency of neurological manifestations of COVID-19 in patients admitted to the Hospital de Urgência de Teresina, describing the different neurological manifestations and their correlations with age, gender, and history of hypertension and diabetes. Methodology: This is a cross-sectional, descriptive and quantitative study conducted during the months of June 2021 to April 2022. Data collection occurred in the medical record archiving service (SAME) at the Hospital de Urgência de Teresina (HUT) in Teresina-PI during the months of August and September 2021. For the research, we analyzed 253 medical records of patients diagnosed with COVID-19, randomly selected among the 736 seen at the HUT between March 1, 2020 and September 30, 2020. Variables analyzed: diagnosis of COVID-19, diagnostic test, age, gender, presence of neurological manifestations, diabetes, hypertension. Results: 50.2% of the analyzed medical records had neurological manifestations, and 40 different neurological symptoms were catalogued. It was not possible to establish a statistical relationship between age, gender and presence of hypertension with neurological symptoms, but there is evidence about diabetes mellitus influencing the presence of the catalogued symptoms. Conclusion: Neurological symptoms have considerable presence for the establishment of the disease and its evolution, with RNC, seizures, anosmia and ageusia being the most common. It was possible to correlate the presence of diabetes with the symptoms presented. The neurological symptoms show direct links with the neurological invasion of COVID-19.